STASIUN SINGGAH SEMANAN INDAH SEBAGAI FASILITAS PENINGKATAN WELLNESS - Greselda Ruby; Andi Surya Kurnia (Jurusan Arsitektur dan Perencanaan, 2020)
Mobility of commuters is one of the factors that causing Jakarta's population density increases. Most of Jakarta residents and commuters spend time with routine activities such as work and study so they do not have free time to create a healthy lifestyle such as exercise and relaxation. This third place project is a facility to improve healthy life and as a layover place because it is supported by its location that is directly related to Jakarta mobility and activities center, named Rawa Buaya commuter train station which is directly connected with office activities. The facilities involve activities to fulfill human physiological needs (Abraham Maslow (1908-1970) in Asmadi (2008:18)) which includes rest, eating, exercise, and relaxation. Thus, the programs that use in the project is to increase physical wellness such as indoor and outdoor sleeping capsules, and food court; mental wellness such as yoga, meditation, zumba, spa, and sauna classes; and social wellness such as game stations, outdoor waiting areas, and charging stations. The design of the thrid place project uses the responses to site approach by considering the orientation to the location of the site at the corner of the road, pedestrian access, and the neighborhood or surrounding buildings. The method is used in forming building masses that pay attention to orientation and natural light, determine the main pedestrian access in the site, place programs near the surrounding functions, and make programs on the ground floor for the public. Keywords: mobility; respond to site; wellness AbstrakMobilitas komuter menjadi salah satu faktor yang menyebabkan kepadatan penduduk Jakarta semakin meningkat. Sebagian besar penduduk dan komuter Jakarta menghabiskan waktu dengan aktivitas rutin seperti bekerja dan belajar sehingga tidak mempunyai waktu luang untuk mewujudkan gaya hidup sehat seperti berolahraga dan berelaksasi. Proyek third place ini menjadi fasilitas peningkatan hidup sehat sekaligus tempat singgah karena didukung dengan lokasi yang berhubungan langsung dengan pusat mobilitas dan aktivitas masyarakat Jakarta yaitu stasiun kereta komuter Rawa Buaya yang terhubung langsung dengan aktivitas perkantoran. Fasilitas tersebut menyangkut kegiatan pemenuhan kebutuhan fisiologis manusia (Abraham Maslow (1908-1970) dalam Asmadi (2008:18)) yang meliputi kegiatan istirahat, makan, olahraga, dan relaksasi. Dengan demikian, program yang diangkat berupa peningkatan physical wellness seperti kapsul tidur indoor dan outdoor, serta food court; mental wellness seperti kelas yoga, meditasi, zumba, spa, dan sauna; serta social wellness seperti game station, outdoor waiting area, dan charging station. Perancangan proyek thrid place ini menggunakan pendekatan responses to site dengan mempertimbangkan orientasi terhadap lokasi tapak di sudut jalan, akses pedestrian, dan neighborhood atau bangunan sekitar. Metode tersebut digunakan dalam membentuk massa bangunan yang menyesuaikan orientasi dan memperhatikan cahaya alami, menentukan akses utama pedestrian di dalam tapak, meletakkan program-program sesuai dengan fungsi sekitar, dan membuat program di lantai dasar sebagai program bersama.